An efficient coding scheme for reversible data hiding in encrypted image with redundancy transfer - Qin, Chuan; Qian, Xiaokang; Hong, Wien; Zhang, Xinpeng (Information sciences, 2019)
Recently, reversible data hiding in encrypted image (RDHEI) has attracted extensive attention, which can be used in secure cloud computing and privacy protection effectively. In this paper, a RDHEI scheme based on redundancy transfer and sparse block encoding is proposed. Content owner first utilizes a specific encryption method, including bit plane disordering, block and pixel scrambling, to encrypt each original block, which not only can transfer the redundancy from MSB to LSB, but also can mask image contents securely. Through an improved sparse matrix encoding method for different types of binary blocks, data hider embeds additional data into the vacated room within LSB of encrypted image efficiently. Separable operations of data extraction, image decryption and image recovery can be conducted on the receiver side based on encryption key and data hiding key. Experimental results demonstrate that our scheme can achieve better rate-distortion performance than some of state-of-the-art schemes.